2018
DOI: 10.3390/cells7050037
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Age-Associated Neurodegeneration

Abstract: The elimination of abnormal and dysfunctional cellular constituents is an essential prerequisite for nerve cells to maintain their homeostasis and proper function. This is mainly achieved through autophagy, a process that eliminates abnormal and dysfunctional cellular components, including misfolded proteins and damaged organelles. Several studies suggest that age-related decline of autophagy impedes neuronal homeostasis and, subsequently, leads to the progression of neurodegenerative disorders due to the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 236 publications
(259 reference statements)
1
96
0
Order By: Relevance
“…Autophagy is a biological process associated with a variety of diseases, such as neurodegeneration and microbial infection . LC3 proteins are essential in regulating autophagy and the LC3‐II/LC3‐I ratio is related to the autophagosome number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a biological process associated with a variety of diseases, such as neurodegeneration and microbial infection . LC3 proteins are essential in regulating autophagy and the LC3‐II/LC3‐I ratio is related to the autophagosome number.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a biological process associated with a variety of diseases, such as neurodegeneration and microbial infection. 28,29 LC3 proteins are essential in regulating autophagy and the LC3-II/LC3-I ratio is related to the autophagosome number. In this study, we checked the LC3B level by both IF and WB; LC3B expression was found to be significantly higher in dental pulp with periodontitis (Figs.…”
Section: Higher Level Of Autophagy In Dental Pulp Of Teeth With Periomentioning
confidence: 99%
“…The efficiency of these clearance mechanisms diminishes with increasing age, with the accumulation of toxic molecules and damaged organelles [43,44,45]. Aging is considered the major risk factor for the insurgence and development of many neurodegenerative diseases, as also confirmed by studies describing the autophagy reduction in aging CNS cells [46,47,48]. For example, mitochondrial complex I (NADH dehydrogenase) dysfunction is strictly correlated to the idiopathic Parkinson’s disease phenotype; similarly, injury of complex II (succinate dehydrogenase) yields the Huntington’s disease phenotype.…”
Section: Brain Processes Involved In Neurodegeneration and Protectmentioning
confidence: 99%
“…The molecular mechanisms of age-related cognitive decline and AD are considered multifactorial and implicate the interaction of genetics and environmental factors acting as susceptibility factors or triggers [2] that promote brain injury accumulation due to their chronicity during ageing. Thus, several cell pathways play a significant role in the progression and development of the cognitive impairment such as transcriptional dysregulation, oxidative stress (OS) [3], inflammation [4], endoplasmic reticulum (ER) stress [5], and autophagy [6], among others. Recently, an increased understanding of the complexity of age-related cognitive decline has led to define the important role of epigenetics in the pathogenesis [7].…”
Section: Introductionmentioning
confidence: 99%